Tax competition in the European Union - Vivek H. Dehejia; Philipp Genschel (Max-Planck-Institut für Gesellschaftsforschung, 1998)
Tax competition poses two problems for international cooperation: defection and distributive conflict. Multilateral cooperation to stop tax competition may fail because states face incentives to renege on their promises or because they face adverse distributional consequences, either of which makes cooperation an unattractive option for them. Conventional wisdom in international relations concentrates on the first problem, highlighting that the problem of tax competition resembles a Prisoner's dilemma. We argue instead that it is the peculiar distributional consequences of tax competition which explain why all attempts to regulate it cooperatively have failed. Combining theoretical analysis with empirical research on the European Union's unsuccessful record of tax cooperation, we show how distributive, within-group conflict amongst potential cooperators interacts with the constraints imposed by a non-cooperating outside world to make multilateral tax cooperation an especially elusive goal for international collaboration. – – Der Steuerwettbewerb stellt die internationale Kooperation vor ein Defektionsund ein Verteilungsproblem. Die Kooperation kann scheitern, weil Kooperationszusagen opportunistisch ausgebeutet werden oder weil Verteilungskonflikte verhindern, daß es überhaupt zu solchen Zusagen kommt. Die bisherige Literatur hat sich fast ausschließlich auf das erste Problem konzentriert. Sie zeigt, daß der Steuerwettbewerb die Struktur eines Gefangenendilemmas hat und erklärt dadurch das regelmäßige Scheitern von Kooperationsversuchen. Wir argumentieren dagegen, daß dieses Scheitern in erster Linie auf Verteilungsprobleme zurückzuführen ist. Modelltheoretische Überlegungen und empirische Befunde aus dem europäischen Binnenmarkt zeigen, wie Verteilungskonflikte sowohl zwischen den potentiellen Kooperationspartnern als auch zwischen diesen und dritten Staaten den Steuerwettbewerb zu einem schwer lösbaren Kooperationsproblem werden lassen.
Keywords: 300